2020
DOI: 10.1002/nag.3070
|View full text |Cite
|
Sign up to set email alerts
|

A SPH framework for dynamic interaction between soil and rigid body system with hybrid contact method

Abstract: A smoothed particle hydrodynamics (SPH) framework for three-dimensional dynamic soil-multibody interaction modeling is presented, where both soils and rigid bodies are discretized using SPH particles. In the framework, soils are modeled using the Drucker-Prager model, while rigid bodies are considered with a multibody dynamics solver. A hybrid contact method suitable for three-dimensional simulations is developed to model the soil-body and body-body frictionless and frictional contacts, where contact forces ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Indeed, in previous SPH modelling of large-scale landslides, the friction angle is usually taken as 30 • [30,31], equivalent to a frictional coefficient of 0.58. It is found in small-scale problems, when applying the common friction coefficient in SPH computing, satisfactory results well-corroborated by experiments can be obtained [10,11,26,28,55,74]. However, it is generally observed that large-scale landslides have run-outs much longer than expected from the usual values of friction coefficient [41][42][43], indicating that the effective friction in large sliding mass is smaller than those obtained in laboratory tests.…”
Section: Influence Of Friction Coefficient µ and Scale Effect In Large-scale Landslidesmentioning
confidence: 69%
“…Indeed, in previous SPH modelling of large-scale landslides, the friction angle is usually taken as 30 • [30,31], equivalent to a frictional coefficient of 0.58. It is found in small-scale problems, when applying the common friction coefficient in SPH computing, satisfactory results well-corroborated by experiments can be obtained [10,11,26,28,55,74]. However, it is generally observed that large-scale landslides have run-outs much longer than expected from the usual values of friction coefficient [41][42][43], indicating that the effective friction in large sliding mass is smaller than those obtained in laboratory tests.…”
Section: Influence Of Friction Coefficient µ and Scale Effect In Large-scale Landslidesmentioning
confidence: 69%
“…In the current work, this approach has been chosen for reasons of simplicity and numerical robustness. An extension to a macroscale approach, i.e., a normal distance-based contact interaction [12,52,53], is possible in a straightforward manner. In addition, also a momentum-based energy tracking method [54] was recently applied for collision modeling of fully resolved rigid bodies [55,56].…”
Section: Remark 18mentioning
confidence: 99%
“…Several friction contact methods allowing arbitrary wall friction angle were proposed for SPH simulations in the past. [44][45][46][47][48] Among them, the hybrid contact method 47,49,50 combines the convenience of point-to-point contact and the accuracy of point-to-segment contact, and is suitable for problems with arbitrary geometry. In this work, it is combined with the regularized SPH model to solve large deformation soil-structure problems.…”
Section: Introductionmentioning
confidence: 99%